2011
DOI: 10.3892/ijo.2011.1084
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-211 is involved in expression of preferentially expressed antigen of melanoma in melanoma cells

Abstract: Abstract. MicroRNAs (miRNAs) are small non-coding RNAs whose aberrations are involved in the initiation and progression of human cancers. To seek unique miRNAs contributing to melanoma tumorigenesis, we investigated the global miRNA expression profile of 7 melanoma cell lines and 3 primary cultures of neonatal human epidermal melanocytes (NHEMs) using the stem-loop real-time PCR method. We found 7 miRNAs that were commonly downregulated and 18 that were upregulated in all of the melanoma cell lines in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Furthermore, enforced expression of miR-211 promoted tumor cell growth at least in part by down-regulating the CHD5 tumor suppressor [ 31 ]. On the other hand, another study showed that miR-211 was a suppressor of melanoma invasion during human melanoma progression [ 34 , 37 , 38 ]. To our knowledge, the role and mechanism of miR-211 in HCC have not been completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, enforced expression of miR-211 promoted tumor cell growth at least in part by down-regulating the CHD5 tumor suppressor [ 31 ]. On the other hand, another study showed that miR-211 was a suppressor of melanoma invasion during human melanoma progression [ 34 , 37 , 38 ]. To our knowledge, the role and mechanism of miR-211 in HCC have not been completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…3A). miR-211, a melanocyte lineage-specific small non-coding miRNA, acts as a tumor suppressor by regulating the activity of oncogenes such as PRAME and KCNMA1 (Mazar et al, 2010; Sakurai et al, 2011). miR-211 suppresses the invasion potential of melanoma cells (Levy et al, 2010; Mazar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have reported modified expression levels of miR-211 in melanoma cells and/or have investigated the functional roles of miR-211 and its target genes [10][12], [17], [18]. A clear correlation has been demonstrated between MITF and miR-211, which we also confirm here: MITF transcriptionally activates, amongst many other genes, the calcium channel TRPM1 (melastatin) and by doing so, the intronic miR-211 is simultaneously up-regulated.…”
Section: Discussionmentioning
confidence: 99%